Pengaruh Literasi Keuangan dan Dukungan Sosial terhadap Keberlanjutan Usaha dengan Entrepreneurial Mindset sebagai Variabel Intervening pada Mahasiswa Wira-Wiri UNJ - Regita Aida Fitri; Agus Wibowo; Ari Saptono (Educational Journal, 2026)
This study aims to analyze the influence of financial literacy and social support on business sustainability with entrepreneurial mindset as an intervening variable among Wira-Wiri UNJ students. This research employed a quantitative approach with a survey method. A sample of 210 students was determined using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using SEM-PLS. The results show that financial literacy has a positive and significant effect on business sustainability and entrepreneurial mindset. Social support does not have a significant direct effect on business sustainability, but it has a positive and significant effect on entrepreneurial mindset. Entrepreneurial mindset has a positive and significant effect on business sustainability. Furthermore, entrepreneurial mindset is proven to mediate the influence of financial literacy and social support on business sustainability. Thus, business sustainability among students is not solely determined by the resources they possess, but rather depends heavily on the formation of a strong entrepreneurial mindset. This study provides implications for incubation program managers to strengthen mentoring based on entrepreneurial mindset development in order to improve student business sustainability.